Attempts to Train Literacy and Numeracy through STEM-based Learning Media Making Training for Science Teachers in Muaraenim Regency - Wiyono, Ketang; Sriyanti, Ida; Patriot, Evelina Astra; Ritonga, Ahmad Fitra; Amri, Iful; Anjani, Rahma Putria; Maylen, Venny; Aulia, Dwi Marwa; Maharani, Senandung Citra; Ramadhona, Tyse; Putri, Apriliski Amanda; Maknun, Lu’luil; Juliansyah, Dendi (Pascasarjana Universitas Mataram, 2024)
This training aims to train literacy and numeracy through making STEM-based learning media on renewable energy material. In addition, teachers are expected to be able to provide innovation in media making, which can be implemented in science learning. The method used in this activity is Participatory Action Research (PAR). Several steps are taken to achieve the set goals, namely 1) giving a pretest or initial test, 2) implementing the service, and 3) giving a final test and evaluation and reflection. This activity was attended by 30 participants who were science teachers and members of the Science MGMP. The results showed that the percentage for the pretest score with 30 participants obtained an average of 47.6%, and the posttest score obtained an average of 93.20%, for a Gain score of 87%. This value represents the interpretation of the practical improvement category. Based on the results of the questionnaire on the level of satisfaction with the implementation of the service, it can be indicated that all teachers feel delighted with the training assistance service activities. This training activity has provided practical solutions to facing the challenges of 21st-century learning, especially in areas with limited facilities.